2009
DOI: 10.1038/nchembio.154
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule that directs differentiation of human ESCs into the pancreatic lineage

Abstract: Stepwise differentiation from embryonic stem cells (ESCs) to functional insulin-secreting beta cells will identify key steps in beta-cell development and may yet prove useful for transplantation therapy for diabetics. An essential step in this schema is the generation of pancreatic progenitors--cells that express Pdx1 and produce all the cell types of the pancreas. High-content chemical screening identified a small molecule, (-)-indolactam V, that induces differentiation of a substantial number of Pdx1-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
346
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(358 citation statements)
references
References 47 publications
6
346
2
4
Order By: Relevance
“…Significant progresses have been made in directing human ESCs to differentiate into pancreatic progenitors and insulin-producing beta cells by stepwise induction [2][3][4][5][6][7][8]. However, although pancreatic progenitors can be efficiently generated from human ESCs, efficient in vitro differentiation into mature functional beta cells that are able to reverse diabetes in animal models has not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Significant progresses have been made in directing human ESCs to differentiate into pancreatic progenitors and insulin-producing beta cells by stepwise induction [2][3][4][5][6][7][8]. However, although pancreatic progenitors can be efficiently generated from human ESCs, efficient in vitro differentiation into mature functional beta cells that are able to reverse diabetes in animal models has not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-based in vitro assays with high human relevance are urgently needed for pre-clinical activities. Previous studies have suggested that ES cells could serve as a screening platform to identify low-molecular-weight compounds that affect endogenous stem cell populations and repair damaged tissue [4,8,10,11,28,29] , and a set of screening protocols is available (ie, the primary screen and the secondary assay). In addition, several cell lines, such as D3 mES cells and H1, H7, and H9 hES cells, are available for drug screening [12,30,31] .…”
Section: Es Cell Models For Drug Screeningmentioning
confidence: 99%
“…As a result, several steroids that promoted hES cell differentiation were identified, and the antihypertensive drug pinacidil was shown to affect hES cell survival. Phenotypic screens can be advantageous because they can be carried out in cells by examining multiple markers and functional changes (for example, cell morphology and behavior) using automated high-content imaging technologies in a high-throughput manner [1,4,36,37] .…”
Section: High-throughput/content Screening (Primary Screen)mentioning
confidence: 99%
See 2 more Smart Citations